MUSYRIF'S COMMUNICATION PATTERNS IN BUILDING THE MORALS OF STUDENTS AT THE DARUL ARQAM MUHAMMADIYAH GOMBARA ISLAMIC BOARDING SCHOOL, MAKASSAR (Karya Ilmiah Mahasiswa (KIMA), 2023)
In the conducted research, the researcher aimed to investigate the communication patterns of the musrif (supervisor) in cultivating the moral character of the students and the forms of moral guidance provided at Darul Arqam Muhammadiyah Islamic Boarding School in Gombara Makassar. This study used a qualitative descriptive research design. The communication approaches utilized were interactive, persuasive, and communicative. The research process involved open-ended interviews, observations, and document analysis, followed by data analysis techniques to understand the communication patterns of the musrif in cultivating the students' moral character and the forms of moral guidance provided at the boarding school. The theoretical frameworks employed in this study included Attribution Theory, BF Skinner's Reinforcement Theory, and the functional group theory. Based on the findings from the research site, the researcher concluded that the observed communication patterns were chain communication, wheel communication, and persuasive communication, which contributed to shaping the students' moral character. The forms of moral guidance provided at Darul Arqam Muhammadiyah Islamic Boarding School include setting a good example, conducting supervision and monitoring, as well as providing guidance and counseling.